Partisipasi Masyarakat dalam Implementasi Kebijakan Penurunan Stunting di Desa Oebafok - Mami Trisari Nggiri; Nursalam Nursalam; Belandina L. Long (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Stunting is a chronic health problem that significantly affects the quality of human resources in the future. Oebafok Village, Rote Ndao Regency, still faces challenges in reducing stunting rates despite the existence of government policies and programs. This study aims to analyze community participation in the implementation of stunting reduction policies using Fung’s (2006) theory through three main dimensions: participant selection, communication and decision, and authority and power.This research employed a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation. The informants consisted of the village head, health workers, posyandu cadres, human development cadres, and parents of toddlers.The findings reveal that community participation remains limited and tends to be formalistic. The mechanism of participant selection is not yet inclusive, as village officials and posyandu cadres dominate the process, while vulnerable groups such as pregnant women, breastfeeding mothers, and poor families are not optimally represented. In terms of communication and decision, communication processes are still mostly one-way from village authorities and health workers to the community, leaving limited room for accommodating community aspirations. Regarding authority and power, decision-making authority is concentrated in the village government, while the community mostly acts as beneficiaries without significant influence in supervision or decision-making.This study concludes that the success of stunting reduction policies in Oebafok Village strongly depends on strengthening active community participation. Therefore, empowerment strategies, direct involvement of vulnerable groups, and participatory two-way communication are needed so that the community can act not only as objects but also as subjects in policy implementation.